Parathyroid Hormone Concentration in Dogs Affected by Acute Kidney Injury Compared with Healthy and Chronic Kidney Disease - Jari Zambarbieri; Erika Monari; Francesco Dondi; Pierangelo Moretti; Alessia Giordano; Paola Scarpa (Veterinary Sciences)
Information about parathyroid hormone (PTH) status in the course of AKI is lacking. In contrast, renal secondary hyperparathyroidism (RSHPT) is a well-known consequence of canine chronic kidney disease (CKD). This study aimed to investigate PTH status in dogs affected by AKI, comparing PTH concentrations between healthy dogs, dogs affected by AKI and dogs affected by CKD. Three groups of dogs (35 affected by AKI, 35 affected by CKD and 41 healthy) were retrospectively included. PTH concentrations were significantly higher in both the AKI and CKD groups (p < 0.0001) compared to healthy ones but without significant differences between the AKI and CKD groups. In the AKI group, increased PTH was detected in 88.6% of dogs. Moreover, in AKI dogs, PTH increases with AKI grading and is correlated with serum creatinine (p < 0.0001; r = 0.67) and phosphate concentrations (p < 0.0001; r = 0.74). PTH in AKI dogs was not correlated with total calcium (tCa), while it was negatively correlated with ionized calcium (iCa) (p < 0.0037; r = −0.53). Higher PTH concentrations also occurred in canine AKI, as reported in canine CKD and human AKI, presumably as a rapid response to ionized hypocalcemia and hyperphosphatemia, frequently reported in our patients. PTH seems not to be a useful tool in distinguishing AKI and CKD.